Pangek Sasau as Cultural Identity in an Expository-Style Documentary Film - Ikrar Qibran Wirja Nugraha; FX Yatno Karyadi; Fadly Rahmadanu; Muhammad Hamdanu Syakirin (KINEMA: Jurnal Komunikasi dan Penyiaran, 2026)
This study discusses the creation of an expository documentary film titled "Pangek Sasau as Cultural Identity in an Expository-Style Documentary." In Minangkabau culture around Lake Singkarak, Pangek Sasau is not merely food, but a local identity that reflects how communities live in harmony with their environment. However, most audiovisual documentation about Lake Singkarak focuses on scenic landscapes and tourism, while local culinary culture has rarely been explored in depth. This creative project aims to demonstrate how Pangek Sasau can represent local cultural identity through a structured and argumentative documentary. The filmmaking process follows four production phases: pre-production (including direct fieldwork and interviews with local fishermen and merchants), production, post-production, and distribution. Applying Bill Nichols' expository mode, this film employs voice-over narration and evidentiary editing to construct a persuasive argument about the preservation of local culture. The findings show that this documentary is effective as an educational tool to introduce and protect traditional culinary heritage from being forgotten by younger generations.